Important organic matter sources and trophic pathways for the nutrition of Hilsa kelee (Cuvier, 1829) and Valamugil buchanani (Bleeker, 1853) in Pangani macro-tidal estuary, Tanzania. Issue 10 (26th November 2018) - Mwijage, Alistidia Paul; Shilla, Daniel Abel; Machiwa, John F.; Zhang, Jing; Fuqiang, Wang; Ying, Wu
ABSTRACT: The study investigated the spatial variation in the main sources of organic matter (OM) and trophic pathways for zooplanktivorous Hilsa kelee and phytodetritivorous Valamugil buchanani in fresh-water-influenced zone versus sea-water-dominated zone of Pangani estuary. The findings indicated significant inter-specific variations in δ 13 C and δ 15 N values (ANOVA, F ≥ 84.3, p < 0.05), fatty acid and dietary compositions (PERMANOVA, pseudo- F ≥ 9.4, p = 0.001) in both estuarine zones. Results also showed significant zonal-intraspecific variations in stable isotopes ( δ 13 C and δ 15 N), FA profile and marginal differences in diet for the V. buchanani while no considerable differences were observed for H. kelee from two estuarine zones. The isotope mixing models and FA biomarkers revealed that the most important carbon sources to the nutrition of H. kelee were derived from microphytobenthos, macro-algae and sea grasses transferred through phytoplankton and detrital trophic pathways. In contrast, C3 terrestrial plants and microphytobenthos were the main carbon source to the diet of V. buchanani ; and were transferred via the benthic and detrital trophic pathways. Therefore, both terrestrial and in-situ OM sources were the main trophic resources base fuelling the planktonic and benthic food webs in Pangani estuary.